Pitch motion control using active suspension during antilock braking - Mahamed, Mohd Hirzan (2022)
Antilock braking system (ABS) is a braking system used to prevent the wheels from locking up while braking, Active suspension is an automotive suspension that could control the movement of the wheels in vertical direction relative to the body of the vehicle by ultilizing an onboard system. In this research, the capability of the active suspension to reduce the pitch motion during antilock braking is studied. A large pitch motion ocours when ABS is applied during hard braking, causing discomfort to the vehicle occupants. To solve the problem, the equations of motion of the seven degrees of freedom (7 DOF) vehicle model are derived. Furthermore, the control systems of ABS and active suspension are designed, where the former is designed by using proportional-integral-derivative (PID) approach. The simulations of the control systems are performed in Matlab Simulink environment. For dry and wet road surfaces, seven plots in time domain are generated based on the simulation results namely vertical displacement, vertical velocity, vertical acceleration, pitch angle, pitch rate, and pitch acceleration of sprung mass, as well as active suspension force during antilock braking. The plots showed significant improvements of using active suspension compared to passive suspension during antilock braking. Histograms for the maximum vertical displacement and pitch angle of the sprung mass for both road surfaces showed improvement of between 86% and 89% for using active suspension compared to using passive suspension during antilock braking. The huge improvements concluded that pitch and vertical motion could be effectively controlled using active suspension during antilock braking.